EFFECT OF IMIDACLOPRID INSECTICIDE RESIDUE ON BIOCHEMICAL PARAMETERS IN POTATOES AND ITS ESTIMATION BY HPLC - Chauhan, Shailendra S.; Agrawal, Sanjeev; Srivastava, Anjana (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Pesticides are known to interfere with the biochemical processes of plants, lowering their food quality. The effects of imidacloprid insecticide (a very commonly used pesticide on vegetables) on some biochemical quality control parameters and some enzyme systems (CAT, PPO and POD) were studied. Estimation of imidacloprid residues in potatoes was done by HPLC. It was observed that insecticide treated potatoes have considerable amount of imidacloprid 0.35 mg/kg at the time of harvesting. Washing potatoes with tap water and boiling for 20min. decreased residue up to 33% and 80% respectively. It was also found that the imidacloprid insecticide treatment decreased the reducing sugar, total phenols, ortho-dihydroxy phenols and ascorbic acid contents of potatoes but increased the total protein content and enzyme (catalase, peroxidase and polyphenol oxidase) activity. Keywords: Imidacloprid, potato, HPLC, biochemical parameters, enzyme activity